2021
DOI: 10.15637/jlecon.8.4.05
|View full text |Cite
|
Sign up to set email alerts
|

Kamu harcamaları ile vergi gelirleri ilişkisi: Pandemi öncesi ve sonrası için bir değerlendirme

Abstract: Türkiye’de pandemi öncesi kamu harcamalarındaki artışlardan dolayı bütçe açıkları yaşanmıştır. Pandemi sonrasında ise yaşanan sokağa çıkma yasakları ile beraber üretimde düşüş yaşanmış ve Haziran 2020’ye kadar vergi gelirleri düşmüştür. Ancak daha sonra vergi gelirlerinde artış yaşanmıştır. Bu dönemde artan vergi gelirlerine rağmen kamu harcamalarında da artış görüldüğünde bütçe açığı devam etmiştir. Bu çalışmanın temel amacı, 2006:Q1-2020:Q1 dönemine ait çeyreklik veriler yardımıyla Türkiye’de kamu harcamala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Many studies investigate the relationship between tax and expenditure when the relevant literature is examined. For example, from these studies, Anderson et al (1986) found that the expenditure-tax hypothesis is valid in the USA, Hondroyiannis and Papapetrou (1996) in Greece, Mithani and Khoon (1999) in Malaysia, Hussain (2004) in Pakistan, Çavuşoğlu (2008) in Turkey, Saunoris and Payne (2010) in the UK, and Kamacı and Kurt (2021) in Turkey. Fasano and Wang (2002) in 6 Gulf cooperation members, Chen (2008) in Taiwan, Eita and Mbazima (2008) in Nabibya, Young (2009) in the USA, Dökmen (2012) in 34 OECD countries, Apergis et al (2012) in Greece, and Yılancı, et al (2020) in Turkey, explain the findings on the tax-spend hypothesis.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Many studies investigate the relationship between tax and expenditure when the relevant literature is examined. For example, from these studies, Anderson et al (1986) found that the expenditure-tax hypothesis is valid in the USA, Hondroyiannis and Papapetrou (1996) in Greece, Mithani and Khoon (1999) in Malaysia, Hussain (2004) in Pakistan, Çavuşoğlu (2008) in Turkey, Saunoris and Payne (2010) in the UK, and Kamacı and Kurt (2021) in Turkey. Fasano and Wang (2002) in 6 Gulf cooperation members, Chen (2008) in Taiwan, Eita and Mbazima (2008) in Nabibya, Young (2009) in the USA, Dökmen (2012) in 34 OECD countries, Apergis et al (2012) in Greece, and Yılancı, et al (2020) in Turkey, explain the findings on the tax-spend hypothesis.…”
Section: Literature Reviewmentioning
confidence: 99%